CENTRAL ASIAN JADIDISM: THE PRESS AND THE FORMATION OF NATIONAL IDENTITY (1906–1917) - Farhod Kenjayev (International Journal of Literature and Language Studies, 2026)
This article analyzes the main directions of the Jadid movement that emerged in Central Asia at the beginning of the twentieth century. The study examines, on the basis of scholarly sources, the Jadid newspapers published in the Turkestan Governorate between 1906 and 1908 (Taraqqiy, Khurshid, Shuhrat, and Tujjor), the development of the New Method educational movement (Usul-i Jadid) in Bukhara, and the emergence of secret reformist organizations. Particular attention is paid to the role of reformist ideas in the formation of national consciousness and the idea of Turkestan unity.